2020
DOI: 10.1080/15384047.2015.1071741
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical implication of cyclooxygenase-2 and E-cadherin in oral squamous cell carcinomas

Abstract: Epithelial-Mesenchymal Transition (EMT) and angiogenesis are crucial events for development of aggressive and often fatal Oral Squamous Cell Carcinomas (OSCCs). Both promote cancer progression and metastasis development, but while the former induces the loss of E-cadherin expression and, hence cadherin switching; the latter produces hematic blood vessel neo-formation and contribute to OSCC cell growth, tumor mass development, and dissemination. Cyclooxygenase-2 (COX-2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Many proinflammatory mediators play a critical role in the suppression of apoptosis, proliferation, angiogenesis, invasion, and metastasis, including TNF superfamily, interleukins, chemokines, MMP-9, VEGF, COX-2 and 5-LOX [35][36][37].…”
Section: Action Of Phlogistic Mediators In Cancer Developmentmentioning
confidence: 99%
“…Many proinflammatory mediators play a critical role in the suppression of apoptosis, proliferation, angiogenesis, invasion, and metastasis, including TNF superfamily, interleukins, chemokines, MMP-9, VEGF, COX-2 and 5-LOX [35][36][37].…”
Section: Action Of Phlogistic Mediators In Cancer Developmentmentioning
confidence: 99%
“…Anesthesia and analgesia may affect EMT [ 25 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. Studies have reported that propofol suppressed EMT in esophageal cancer, choriocarcinoma, breast cancer, thyroid cancer, lung cancer, gastric cancer, hepatocellular carcinoma (HCC), renal cell carcinoma (RCC), prostate cancer, and oral squamous cell carcinoma cells [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Tumor Factors: Emt Hypoxia-inducible Factor-1α (Hif-1α) Matr...mentioning
confidence: 99%
“…COX-2 decreases the expression of E-cadherin and leads to phenotypic changes in epithelial cells enhancing their carcinogenic potential. This study was performed by a tissue microarray of oral squamous cell carcinomas from human patients [102].…”
Section: Prostaglandins In Other Cancermentioning
confidence: 99%